Low concentration of inorganic fullerene tungsten sulfide nanofiller to achieve cost‐effective and significant enhancement on thermal and dynamic mechanical properties of perfluoroalkoxy nanocomposites. Issue 10 (14th August 2021) - Chen, Ding; Bai, Zhihao; Feng, Chen; Ma, Zhiyuan; Wang, Nannan; Zhu, Yanqiu
Abstract: Special insulated wires beyond the conventional pure perfluoroalkoxy (PFA) polymers need to be developed to meet the increasing thermal management and mechanical performance requirements. Advanced PFA nanocomposites enhanced by inorganic fullerene tungsten sulfide (IF‐WS2 ) nanoparticles have been fabricated by melt blending and hot press processes. Benchmarked against the PFA, the presence of IF‐WS2 nanoparticles in the composites resulted in a maximum tensile strength of 21.35 MPa and a maximum elongation at break of 275%, which are 66% and 149% higher than those of pure PFA, respectively. The nanocomposites with 0.5 wt% IF‐WS2 achieved a 17.5% increase in storage modulus, 26.8°C increase in the onset melt temperature, while 1 wt% IF‐WS2 increased the glass transition temperature ( T g ) by 3.4°C and the crystallinity ( χ c ) by up to 34.4%. And when the additional amount of IF‐WS2 nanomaterials is 0.25%, the best combination of performance is obtained. Abstract : Fabrication procedure of inorganic fullerene tungsten sulfide (IF‐WS2 ) nanoparticles and IF‐WS2 /perfluoroalkoxy nanocomposites.